Emergency department crowding: why do patients walk-in?. Issue 3 (4th May 2021) - Brasseur, Edmond; Gilbert, Allison; Servotte, Jean-Christophe; Donneau, Anne-Françoise; D'Orio, Vincent; Ghuysen, Alexandre
ABSTRACT: Objectives : For years, general practitioners (GP) shortage and patients' increasing demand for acute care have been associated with Emergency Department (ED) crowding. Indeed, EDs admissions for non-emergency care seem to constantly increase. Surprisingly, the rationale for patients own decision to directly reach EDs over primary care have been poorly investigated to date. Methods : We conducted a study on patients admitted in two University EDs during nine consecutive days. Patients were asked to answer a survey about their frames for coming and if they were self-referred, referred by a GP, a specialist or after calling the Emergency Number. Results : During the study period, 68.0% of patients were self-referred, 17.0% referred by their GP, 8.5% by a specialist and 7% after an emergency call. 51.0% of the self-referrals thought EDs were the appropriate location to deal with their health problem and 24.0% because of a better accessibility. We noticed that 15.0% of the incomings looked for specialized care and 4.22% reported that the stress had motivated them. Of note, 4.6% of the patients were attracted by the hospital reputation. Financial concerns represented less than 1.0% of the motives invocated. Conclusion : We found that patients' self-perceived severity of illness is the predominant frame to each the ED when they face needs for acute care. EDs' accessibility as compared with other facilities also seems to encourage patients to come to the ED. Other factors such as the hospital reputation or patients' stress tend to influence ED attendance but to a much lesser extent.